PENGARUH MATH ANXIETY DAN SELF EFFICACY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI SPLDV - Naura Syifa Salsabila; Siska Imelda; Virda Nurmalia; Rosida Rakhmawati Muhammad; Bambang Sri Anggoro; Dona Dinda Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Problem solving is the process of finding a solution to a problem through the stages of: problem identification, cause analysis, development of alternative solutions, selection of the best solution, and implementation and evaluation of the results. This process requires critical and systematic thinking to achieve effective results. This study is intended to analyze the effect of math anxiety and self-efficacy on students' ability to solve mathematical problems on the material